2024
DOI: 10.1186/s12905-024-02915-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of modern menstrual methods and related unmet needs among college going women in Coimbatore district: a descriptive cross-sectional study

Thavansree Durairaj,
Periasamy Aparnavi,
Seetharaman Narayanan
et al.

Abstract: Objectives The primary objectives were to determine the proportion of modern menstrual method (MMM) users among college going women in Coimbatore district, Tamil Nadu; and to estimate the unmet needs associated with use of MMMs in comparison with other menstrual hygiene methods (MHMs). We also assessed the factors that determine MMM use among college going women. Methods This was a descriptive cross-sectional study conducted among college going wom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…It revealed that a staggering 96.03% relied on non-biodegradable sanitary pads. These findings echo similar trends observed in studies among college-going women done by Durairaj et al, reaffirming the dominance of sanitary pads as the preferred method of menstrual protection [ 14 ]. Despite the growing dialogue on modern alternatives like menstrual cups and tampons, their adoption remains dismally low, with only one participant reporting the use of a menstrual cup in the present study - a trend consistent with existing literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It revealed that a staggering 96.03% relied on non-biodegradable sanitary pads. These findings echo similar trends observed in studies among college-going women done by Durairaj et al, reaffirming the dominance of sanitary pads as the preferred method of menstrual protection [ 14 ]. Despite the growing dialogue on modern alternatives like menstrual cups and tampons, their adoption remains dismally low, with only one participant reporting the use of a menstrual cup in the present study - a trend consistent with existing literature.…”
Section: Discussionsupporting
confidence: 90%
“…Reusable alternatives such as cloth pads, banana fiber pads, compostable sanitary pads, period panties, and menstrual cups offer promising solutions to mitigate the environmental impact of menstrual waste. Among these options, menstrual cups stand out as a safe, effective, and eco-friendly choice, with studies worldwide affirming their efficacy and safety [ 10 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study modern methods including cups and tampoons had lesser unmet needs than those using sanitary pads. 14 A similar report of cups allowing better mobility and freedom of activities than pads was reported from a refugee camp in Uganda. 21 A high majority of 96.3% were using sanitary pads and a similar proportion has been reported by other studies in India.…”
Section: Discussionmentioning
confidence: 67%
“…A detailed study methodology has been explained in an earlier publication of this study. 14 Study tools & Data collection: After a detailed literature review and discussions with subject experts a predesigned, semi-structured questionnaire was developed to capture socio-demography, menstrual talks, unmet needs of menstrual hygiene practices (using Menstrual Practice Needs Scale (MPNS-36)) and choice of menstrual hygiene methods. The questionnaire was administered using Google Forms.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%